The preparation and biocompatible evaluation of injectable dual crosslinking hyaluronic acid hydrogels as cytoprotective agents. Issue 28 (25th June 2019) - Cao, Wanxu; Sui, Junhui; Ma, Mengcheng; Xu, Yang; Lin, Weimin; Chen, Yafang; Man, Yi; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract : An injectable dual crosslinking hyaluronic acid hydrogel was prepared by a thiol–ene click reaction and conversion between sulfhydryl and disulfide bonds. This injectable hydrogel exhibits good biocompatibility and potential biomedical applications. Abstract : Injectable hydrogels attract a great deal of attention due to their in situ formation in vivo, which minimizes the risk of major trauma during the surgical procedure as compared to traditional hydrogel scaffolds. Click chemistry is widely used in the preparation of injectable hydrogels, although some of them require photoinitiators or catalysts that may be cytotoxic and impair the proliferation of encapsulated cells. In the present study, an injectable dual crosslinking hydrogel was designed by a thiol–ene click reaction and conversion between sulfhydryl and disulfide bonds at a neutral pH. The sulfhydryl group and acrylate group were successfully grafted onto HA and characterized using FT-IR and 1 H-NMR. The gelation time, morphology, injection force, swelling, degradation, mechanical properties and drug release behavior of the hydrogel varied with the molecular weight of the hydrogel ( M w = 0.1, 1.0, 2.0 MDa). MTT, FDA/PI staining and scanning electron microscopy (SEM) showed that the encapsulated L929 proliferated well in different molecular weight hydrogels. It was also observed that in a low molecular weight (0.1 MDa) hydrogel system, the cells were better distributed and secreted more extracellular matrix. Subcutaneous injection in mice also demonstrated that hydrogels could support the proliferation of encapsulated L929 cells in vivo, and no significant infiltration of peripheral cells into the interior of the material was observed. These results indicate that this injectable hyaluronan-based hydrogel is an excellent cell protectant and exhibits good biocompatibility, with potential for biomedical applications such as cell delivery and postoperative anti-adhesion.